2006
DOI: 10.1002/bjs.5344
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral recurrence and prognostic factors in familial non-BRCA1/2-associated breast cancer

Abstract: Stage at detection was a key determinant of prognosis in familial non-BRCA1/2 breast cancer, whereas contralateral cancer was not. Risk-reducing contralateral mastectomy did not significantly improve survival, but early detection can. Decisions on breast-conserving treatment can be made on the same grounds in patients with familial and sporadic breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Our results are concordant with a previous retrospective study on a cohort of 327 familial non- BRCA1/2 breast cancer cases [12,13]. These authors found incidences of metachronous contralateral breast cancers after 10 years that were similar to those in sporadic breast cancer patients (that is, 6.4% versus 5.4%, respectively).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are concordant with a previous retrospective study on a cohort of 327 familial non- BRCA1/2 breast cancer cases [12,13]. These authors found incidences of metachronous contralateral breast cancers after 10 years that were similar to those in sporadic breast cancer patients (that is, 6.4% versus 5.4%, respectively).…”
Section: Discussionsupporting
confidence: 92%
“…While the risk for second primaries has been studied in BRCA1 or BRCA2 mutation carriers, preliminary data indicate that the risk of contralateral breast cancer is not significantly elevated in patients with familial breast cancer, who tested negative for BRCA1/2 mutations [12,13]. Despite these data and although the latter group accounts for the majority of women with familial breast cancer, there is a rising demand for prophylactic bilateral or prophylactic contralateral mastectomy in these women [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…When a tumor doubles its volume four times, tumor size at imaging will increase from 2 to 5 mm or from 4 to 10 mm. This is a detectable change, and although in studies the rate of distant metastases increased much faster with increasing tumor size in high-grade cancers (as often seen in BRCA1/2-related tumors) than in low grade cancers, as long as the tumor was detected in the 2-to 10-mm size range the prognosis was excellent (8)(9)(10)18). In our BRCA1 group under age 40, however, mean tumor pathology size was 18 mm, a size at which the risk of metastases is relatively high for these usually high-grade cancers (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…The survival of women diagnosed with breast cancers <1 cm and with negative lymph nodes is excellent. In BRCA mutation carriers and in familial high-risk patients, tumor size at detection is a key predictor of survival (8,9) and mortality risk may be reduced by early tumor detection (10).…”
mentioning
confidence: 99%
“…Of the approximately 300,000 U.S. citizens, about 5 million (<2%) are Jewish, and the proportion is lower in the South (Berkowitz et al 2003). Also, contralateral breast cancer may not be a specific marker for positive genetic testing (Keim and Ferguson 2007; Tilanus-Linthorst et al 2006). Since none of the participants reported having genetic testing themselves, it seems unlikely that their relatives had genetic testing, but that is still a possibility.…”
Section: Discussionmentioning
confidence: 99%